Estilos de afrontamiento en estudiantes de padres divorciados de educación general básica de la unidad educativa San Felipe Neri. Riobamba, octubre 2017- marzo 2018 - Andrade Cáceres, Paulina Isabel (2018)
In the present investigation the styles of confrontation with respect to the divorce of their parents in the students of eighth and ninth years of General Basic Education of the Educational Unit San Felipe Neri of the City of Riobamba were studied, it was considered important to approach this subject since Preprofessional practices were carried out in the institution and it could be shown that there was a considerable number of students who came from divorced parents and with this there has been a direct affectation in some adolescents. It was essential to study the predominant coping style in the students since they are going through a phase of changes at the biopsychosocial level and for this reason we selected the study population with a sample of 300 students randomly intentional. The proposal was planted in order to know the number of students who come from divorced parents through a survey, to identify the coping style was applied the test called ACS (Adolescent Coping Scale), The methodology was qualitative approach , the non-experimental design; the type of research was correlational, for the transverse time, for the place: field and bibliographic. As a conclusion it was determined that the coping style of the students of divorced parents in the institution was directed to the resolution of problems.